Teknik Komunikasi Persuasif dalam Pengajaran - Ahmad Zaenuri (JP : JURNAL PENDIDIKAN, 2017)
This article explain aboute the persuasive communication on instruction. Persuasive communi-cation is an effective communication technique in education, because by using these communication techniques students are able to do something that they are desired by a teacher without feeling any burden and fear. The learning process is actually the activity of communication and social interactions between teachers and students in order to deliver the knowledge face to face either in small groups and large groups. In learning activities, there is teaching techniques so that the learning objectives are able to be achieved. The activity of persuasive communication in education is a communication that orients to students’ psychological in order to raise the awareness to learn for their future and the Indonesian’s drem. The teacher should broad themselves with the theories of persuasive communi-cation to make them effective communicator. The communication and education are not much difference. The differences are just the purpose of communication and education. From the effects’ point of view, the goal of communication is general while the goal of education is specific. The purpose of education is specific; to raise the knowledge of someone about something until that person is able to master it while the purpose of communication is to change the attitudes and opinions.Keywords; Communication, Education, Persuasive